APPLICATION OF PRUDENTIAL BANKING TO ELIGIBILITY FOR THE DISTRIBUTION OF KUR UMKM BSI BRANCH DIPONEGORO BANDA ACEH. STUDY ON TESTING THE INCOME AND PROFITABILITY OF DEBTOR CUSTOMERS' BUSINESSES - Adzkia, Khaliza; Mukdin, Khairani; Sholihin, Riadhus (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
This research emphasises the importance of testing customer income and profitability in ensuring financing eligibility and supporting the financial stability of banks and the development of MSMEs in Indonesia. This reseacrh aims to ensure that the financing disbursement process is carried out effectively and in accordance with prudential banking principles with legal provisions. This research method is normative empirical. The results of the research showed that the distribution of KUR was in accordance with the mandate of articles 8 and 29 of Law No. 10 of 1998 on Banking and article 23 of Law No. 21 of 2008 on Sharia Banking. This can be seen from the application of KUR distribution at BSI Diponegoro Branch Banda Aceh which is carried out strictly through testing with five main stages, namely BI checking, surveys, business feasibility analysis, analysis of collateral feasibility, the committee process with the leadership and the analysis of MSMEs income and profitability by paying attention to income sources, income stability, sales trends, seasonal patterns, sales targets, profit patterns, bank transaction history and bank transaction frequency.